DAMPAK GLOBALISASI TERHADAP PEREKONOMIAN GLOBAL - Muammil Sun'an (MediaTrend, 2010)
Globalization has generated a process of capitalism of nation-state towards a very new phase. Since 1992, world has related each other in one social system through commercial and financial activities integrated in an international market. But since 1960 until now, the statement is getting more acceleration, economic activities on the world has begun a way to a new global economy. The implementation of economic activities started from the transaction of goods, services, and factors of production, and then followed by more economic integration among countries.Globalization of economy causes a dominant role of non-state economic actors with great international economic activities, called multinational corporation or (transnational corporation, TNCs). As a result, economic activities on the world are dominated by the businessmen who have internationalized their activities through expansion, exporting so many products and sales to many countries where they (the businessmen/companies) don't have loyalties to a nation-state particularly and do their investment and run their businessmen in "global" market where they can get a great number profits.Neo-Liberalisms think that by the reincreasement of free market and ideas of laisses-faire global corporation will cause organized international production and maximalization of global welfare without overproduction capacity. International communities are now growing toward over global economy and are dependent each other. They will support the welfare, international relationship, and world peace.